Epistemologi Fikih Kelautan Ulama Nusantara - Athoillah Islamy; Zaimuddin Zaimuddin (Inovasi-Jurnal Diklat Keagamaan, 2021)
Although crab is seen as an animal that has great benefits for the health of the human body, there are differences among scholars regarding the law of consuming it. This study intends to explore and identify the construction of Islamic legal thought by one of the Javanese coastal ulama in the 19th century AD regarding the legal status of the crab halal. The cleric in question is named Kiai Muhammad Anwar or who is often called Kiai Anwar Batang. This research is a qualitative research in the form of literature review. This Islamic legal research is included in the category of normative-philosophical Islamic law research. The data source is the Book of Aisyul Bahri by Kiai Anwar Batang, and various relevant scientific researches. The approach used is a philosophical approach to Islamic law by using a systems approach as proposed by Jasser Auda. This study concludes that the Islamic legal thinking of Kiai Anwar Batang regarding the halal status of crab is built on a universal interpretation of the legal message in verse 96 of the al-Maidah letter and is strengthened by various opinions of scholars regarding halal law for all types of aquatic animals. However, it does not stop at the approach to interpretation of the nas, Kiai Anwar Batang also conducts empirical research in the field with observations of the life of crab. He saw that crab is animal that can only live briefly on land, not animal that live in two realms (water and land). Therefore, it is halal for consumption.